(untitled) (Journal of the College of Education for Women, 2019)
Suzanne Collins’ novel The Hunger Games suggests a new logic of victory and set a distinguished focus on the unique personality of her heroin which brings to the mind the permanent correlation between all moral values. The Hunger Games World seems to be much more like one big bowl as it links the past, present, and the future. An Intertextual reference is interwoven in the present research as it brings Golding’s Lord of the Flies to the surface, and it highlights certain similarities between the two texts. In which Ralph, Piggy and Simon in Golding’s Lord of the Flies are the incarnations of stable moral values and hope of surviving ethics and rules in a chaotic and turmoil world. The events in Collins’ book prove that a character is refined and enriched by the challenges he/she overcomes through his/her lifetime. It presents a picture of contemporary life which is characterized by a condensed intellectual and spiritual crisis. The word "Hunger" in the novel is metaphorical; it denotes the uncontrollable need for political freedom, a healthy social system and equal opportunities in life. In the world of Panem’s District 12, bread means hope.it represents a survival from hunger. The elites of Panem use hope as a method of control. Katniss embodies the hope of a better world, a liberated Panem.